Meningkatkan Keterampilan Menulis Tembang Pocung Dengan Penerapan Strategi Brainwriting Siswa Kelas XI SMAN 1 Sulang (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Javanese language learning is one of the lessons that still underestimsted. aatherefore it is very necessary to optimize the learning of Javanese languge and literature. One way to optimizelearning Javanese is with interesting and fun teaching methods. To increase motivation to study and improve writing skills, tembang pocung with the application of brainwriting strategies in classXI students of SMA Negeri 1 Sulang in particular. Brainwriting strategies can bring an innovative learning atmosphere, create fun learning and can motivate students to have more opportunities to exploit writing songs freely and broadly, according to the ability level of each students. The writer hopes that the implementation of a brainwriting strategy in learning can reduce boredom, generate student enthusiasm so that it will have a positive impact on the on the learning process as the writer hopes. The method used is descriptive method because this research describes how a learning technique is applied and how the desired results can be achieved. After students try to use the brainwriting method, the expected value is obtained. Based on the discussion above, the application of the brainwriting strategy to the writing skills learning process, especially the material for writing tembang pocung can improve students achievement.